Quantitative analysis of minerals in the selected formulations of spices and herbs using ICP-MS - Shirazi, Ovais Ullah; Khattak, Muhammad Muzaffar Ali Khan; Shukri, Nor Azwani Mohd. (Progress in Nutrition, 2016)
The purpose of this study was to assess minerals contents of three different formulations of spices and herbs, that is mixed herbs (F1), mixed spices (F2) and mixed spices & herbs (F3) predominantly formulated for general health and wellbeing. Minerals namely K, Ca, Mg, Cr, Mn, Zn, Cu and Fe, which are considered vital for good health were studied. The samples were processed, digested and the aforementioned minerals were quantitatively analyzed in the said formulations of spices and herbs by using ICP-MS. The analysis was performed in triplicates and the post-hoc (tukey) test was applied to determine the mean difference amongst the mineral contents of the three formulations with p